COOPERATIVE LEARNING TALKING CHIPS TOWARDS STUDENTS’ CRITICAL THINKING IN SPEAKING AT SMAN 9 MATARAM - Muhammad Asrul Hasby (Journal of English Education and Literature, 2024)
Critical thinking is the activity of training the mind to explain how to use the function of the brain to publish ideas. Hence the focus of critical thinking is to tell the argument. Consequently, the ability to think critically is very important such as the ability to analyze and solve problems, especially in learning English. This research aims to find out cooperative learning talking chips towards students’ critical thinking in speaking at SMAN 9 Mataram. The research design that has carried out is the Nonequivalent Control Group Design. The population in this study are all students of class IX MIA SMAN 9 Mataram which consisted of five 5 classes by the total 127 students and the sample were MIA 2 with 26 students as the control class and MIA 4 with 25 students as the experimental class. The result was Based on the observations of researchers, this is due to students who still lack students' interest in the learning process. In addition, students are also still lacking discipline in doing assignments and following the learning process. And also because the lesson hours are at the end of the learning process which causes students to lack focus due to fatigue and get bored quickly plus at that hour students are more likely to want to go home quickly. Apart from students, teachers are also not optimal in delivering and mastering the material and learning process, not fully implementing the syntax of Cooperative Learning Talking Chips.